NURSES' ANXIETY RELATED TO COVID-19 WITH SPIRITUALITY - Heru, Maulidiyah Junnatul Azizah; Jatimi, Atika (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Introduction: Nurses as health care providers with the nature of their profession are very difficult to avoid close contact with their patients. The high risk of exposure to Covid-19 infection and other factors affect the psychological well being of nurses which has an impact on the mental status of nurses who feel anxious all the time. Satisfied spiritual needs can improve coping to deal with difficult or challenging situations. Objective: The purpose of this study was to analyze the relationship between nurses' anxiety related to Covid-19 with spirituality. Methods: The research design is correlational with a cross-sectional design approach. The sample in this study was 35 respondents with skills using purposive sampling technique and data analysis using Spearman. Results: Based on the results of the study, it is known that the anxiety level of nurses is in the moderate anxiety category of 40.0%. And the spiritual level of nurses is in the high category as much as 51.4%. Then the data was analyzed using the Spearman test with a significance error of 0.05 and obtained p-value (0.00 < (0.05) so that it can be concluded that there is a relationship between nurses' anxiety related to Covid-19 and spirituality in the Inpatient Room. Conclusion: Fulfilled spiritual needs for nurses during a pandemic can improve coping to face difficult or challenging situations. In this pandemic condition spiritual life will be a very important part in overcoming anxiety.